Analisis Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Smartphone Vivo Pada PT. Rappang Jaya Abadi di Mall Metropolitan Bekasi (Mulia Pratama, 2023)
The purpose of this study is research to determine and analyze the effect of product quality and promotion on purchasing decisions for Vivo smartphones at PT. Rappang Jaya Abadi at Mall Metropolitan Bekasi. The population in this study are consumers of PT. Rappang Jaya Abadi, totaling 130 people and the sample used in this study were 57 people obtained from the sum of the slovin formula. Data collection techniques in this study used questionnaires, interviews and data analysis techniques in the study using Validity Test, Reliability Test, Multicollinearity Test, Normality Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Hypothesis Test through T Test, F Test, and Coefficient Test Determination (R2) using the help of the SPSS version 26 program. The partial test results show that the product quality variable (X1) shows a Tcount value of 3.232 > Ttable 2.004 and a significance value of 0.002 <0.05. So it can be concluded that product quality has a positive and significant influence on purchasing decisions. Meanwhile, the promotion variable (X2) shows a Tcount value of 9.621 > Ttable 2.004 and a significance value of 0.000 <0.05. So it can be concluded that promotion has a positive and significant influence on purchasing decisions. Based on the results of the F test, it is known that the Fcount value is 152.878 > Ftable 3.17 and a significance value of 0.000 <0.05. So it can be concluded that product quality and promotion together have a positive and significant influence on purchasing decisions.